2013
DOI: 10.1097/cad.0b013e32835f705f
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 plays a role in the upregulation of CD44 expression through extracellular signal-regulated kinase signaling in human colon cancer cells

Abstract: Our previous study has shown that the activity and expression of sphingosine kinase (SPHK) regulated the sensitivity of human colon cancer cells to the chemotherapeutic oxaliplatin (L-OHP). In addition, the cancer stem cell marker CD44 increases cell resistance to anticancer drugs. Here, we use colon cancer cell lines to examine the relationship between SPHK1 activity and CD44 expression.CD44 expression was measured by western blotting and quantitative PCR in two human colon cancer cell lines: L-OHP-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Combination chemotherapy is an important strategy for improving therapeutic outcomes and reducing the side-effects of anticancer drugs. Various studies have indicated the possible utility of combining anticancer drugs with agents associated with the SK1/S1P pathway for cancer therapy (22)(23)(24). The combination of SK inhibitors, including siRNA, with anticancer drugs has been shown to be effective against drug-resistant colon cancer (22,23) and pancreatic cancer (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination chemotherapy is an important strategy for improving therapeutic outcomes and reducing the side-effects of anticancer drugs. Various studies have indicated the possible utility of combining anticancer drugs with agents associated with the SK1/S1P pathway for cancer therapy (22)(23)(24). The combination of SK inhibitors, including siRNA, with anticancer drugs has been shown to be effective against drug-resistant colon cancer (22,23) and pancreatic cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated the possible utility of combining anticancer drugs with agents associated with the SK1/S1P pathway for cancer therapy (22)(23)(24). The combination of SK inhibitors, including siRNA, with anticancer drugs has been shown to be effective against drug-resistant colon cancer (22,23) and pancreatic cancer (24). The combination of doxorubicin and SK1-locked acid-antisense oligonucleotides has also been shown to be effective against gastric cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…In a model of colitis-associated cancer, S1P 1 signaling was necessary for persistent activation of nuclear factor-kB and signal transducer and activator of transcription3 transcription factors needed for maintaining the chronic infl ammatory state and could be blocked by FTY720 treatment ( 171 ). In human colon cancer cells, expression of the chemotherapeutic resistance and cancer stem cell marker CD44 was regulated by S1P 2 -induced ERK phosphorylation ( 172 ). Interestingly, FTY720 treatment impaired the mucosal immune response to the extracellular bacterium, Citrobacter rodentium , including decreased DC numbers, as well as macrophages and T cells in the colon, while increasing bacterial burden ( 173 ).…”
Section: Nervous Systemmentioning
confidence: 99%
“…In colon cancer, S1PR1 is up-regulated by persistent activation of NF-KB and STAT3 transcription factors, resulting in colitis-associated colon cancer (Liang et al, 2013). In addition, S1PR2-induced ERK phosphorylation up-regulates CD44, a cancer stem cell marker in HCT116 human colon carcinoma cells (Kawahara et al, 2013). In prostate cancer, activity of S1PR5 induces autophagy through generating endoplasmic reticulum stress in human prostate cancer PC-3 cells (Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%